Mixed Chelate Complexes of Nickel(II) and Copper(II) - Minati Satpathy, Ms.; Pradhan, B. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes· of Ni2+ and Cu2+ containing bis-salicyl-aldehyde ethylene diamine or salicylaldehyde semicarbazone and neutral monodentate ligands of the type [Cu(SB)L1], [Cu(SB)L2], [Cu(SB)L3] and [Ni(SB)L1], [Ni(SB)L2] and [Ni(SB)L3] were synthesised. The compounds were characterised on the basis of their elemental analyses, molecular weight, conductivity, magnetic moment,infrared and electronic spectral data.